Devastating recurrent brain ischemic infarctions and retinal disease in pediatric patients with CD59 deficiency. (November 2015) - Ben-Zeev, Bruria; Tabib, Adi; Nissenkorn, Andreea; Garti, Ben-Zion; Gomori, John Moshe; Nass, Dvora; Goldshmidt, Hanoch; Fellig, Yakov; Anikster, Yair; Nevo, Yoram; Elpeleg, Orly; Mevorach, Dror
Abstract Identification of CD59 p.Cys89Tyr mutation in 5 patients from North-African Jewish origin presenting with chronic inflammatory demyelinating polyradiculoneuropathy like disease and chronic hemolysis, led us to reinvestigate an unsolved disease in 2 siblings from the same origin who died 17 years ago. The two patients carried the same CD59 gene mutation previously described by our group. These children had quiet similar disease course but in addition developed devastating recurrent brain infarctions, retinal and optic nerve involvement. Revising the brain autopsy of one of these patients confirmed the finding of multiple brain infarctions of different ages. CD59 protein expression was missing on brain endothelial cells by immunohistochemical staining. This new data expands the clinical spectrum of CD59 mutations and further emphasizes the need for its early detection and treatment.